(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
This research paper demonstrates untraditional learning and teaching method that is developed from combination of experimentation, usage of computer simulations and problem based learning. Taking all previously mentioned methods together there can be created very successful learning environment which provides students to master electromagnetism more effectively. Research focuses on proper use of data acquisition modules and computer simulations in PBL teaching method. Based on the results of the research experimental PBL in various cases provides better learning outcomes, but there are also a few occasions where the results aren’t so pleasing. Overall PBL provides results that are at least as promising as results of other teaching and learning methods. Therefore this method will be utilized in Liepaja University to teach physics, especially electromagnetism.